Public Perception and Digital Pressure on Regional Heads: The Melki Laka Lena Phenomenon - Mira Natalia Pellu; Asrianto Asgaf (Jurnal Studi Sosial dan Politik, 2025)
The transformation of political communication in the digital era has shifted regional leaders from operating solely within bureaucratic structures to navigating rapidly evolving public perceptions shaped by social media. This article examines the dynamics of public perception toward Melki Laka Lena as the Governor of East Nusa Tenggara by employing three main frameworks: media logic to understand how political communication becomes increasingly symbolic and easily circulated, affective publics to explain the role of emotions, satire, and public disappointment in digital conversations, and network society to analyze how meanings of leadership are reproduced through digital user networks. This study uses a qualitative case study approach through textual-multimodal reading and digital discourse analysis of social media posts, screenshots of public conversations, and comment sections. The findings reveal that public perception is shaped more by communication symbols, visual representations, collective emotions, and online interactions than by substantive discussions of government policies. Social media has ultimately evolved into a space where digital pressure and public perception toward regional leaders are continuously constructed.